Groping around in the dark for adequate COPD management: a qualitative study on experiences in long-term care - Sara Lundell; Ulla-Maija Pesola; André Nyberg; Karin Wadell (BMC, 2020)
Abstract Background Chronic obstructive pulmonary disease (COPD) is one of the most common and deadliest chronic diseases worldwide. Since COPD is a chronic and progressive disease, treatment is necessary throughout life. For people with COPD who cannot live independently, long-term care facilities are often required. However, knowledge is very limited about aspects of importance for effective COPD management in these settings in accordance with current treatment guidelines. The aim of this study was to explore aspects of importance in long-term care facilities for providing interventions according to treatment guidelines for people with COPD, from the perspective of healthcare professionals, in an effort to prove novel knowledge that could be used to facilitate implementation of treatment guidelines in these settings. Methods A qualitative study was performed in northern Sweden. In Sweden, municipalities are responsible for providing long-term care. Interviews with 36 healthcare professionals (nurses, physiotherapists, occupational therapists and dieticians) in municipal healthcare were conducted and analysed using qualitative content analysis with triangulation by the authors. Results The overarching theme that emerged from the analysis was Groping around in the dark for adequate COPD management. This represents healthcare professionals' experiences of working with a complex diagnosis somewhat overlooked in the municipal healthcare, an underdog in the healthcare system. The groping around in the dark theme further represents the healthcare professionals' lack of COPD-related competence, lack of interprofessional collaboration, and insufficient communication with the county council. The fragile group of people with COPD and their relatives were considered in need of support adapted to their context, but routines and resources for COPD management were limited. This lack of routines and resources also resulted in professionals being pragmatic and adopting short-term solutions without focusing on specific needs related to the diagnosis. Conclusions The COPD management in long-term care settings showed several insufficiencies, indicating a large gap between clinical practice and treatment guidelines for COPD. It is crucial to improve COPD management in long-term care settings. Consequently, several actions are needed, such as increasing professional competence, establishing new routines, acknowledging and making COPD a higher priority, as well as adapting treatment guidelines to the context.